👤

Math How do you use GEMDAS rule in performing operations?​

Math How Do You Use GEMDAS Rule In Performing Operations class=

Sagot :

Answer:

For example:

(5-2) + 2^2- (3)(1) ÷ 1=

Using GEMDAS RULE

1. focus first on Group

the Group there is (5-2)

= 3 + 2^2 - (3)(1) ÷ 1

2. next is Exponent

= 3 + 4 - (3)(1) ÷ 1

3. Multiplication

= 3 + 4 - 4 ÷ 1

4. Division

= 3 + 4 - 4

5. Addition

= 7 - 4

6. Subtraction

= -3

Step-by-step explanation:

hope it will help you thank you :))

Answer:

✒️TRANSLATION

••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••

\large\underline{\mathbb{DIRECTIONS}:}

DIRECTIONS:

Translate each into a mathematical statement. Use k as the constant of variation.

••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••

\large\underline{\mathbb{ANSWERS}:}

ANSWERS:

#1: Q varies jointly as p and r.

\large \rm Q = kprQ=kpr

\:

#2: R varies directly as t and inversely as w.

\begin{gathered} \large\rm R =\frac{\,kt\,}{w} \\ \end{gathered}

R=

w

kt

\:

#3: S varies directly as m and inversely as the square of b.

\begin{gathered} \large\rm S =\frac{\,km\,}{b^2} \\ \end{gathered}

S=

b

2

km

\:

#4: T varies directly as the square of v and inversely as z.

\begin{gathered} \large\rm T =\frac{\,kv^2\,}{z} \\ \end{gathered}

T=

z

kv

2

\:

#5: A varies directly as the square of b and inversely as the square of c.

\begin{gathered} \large\rm A =\frac{\,kb^2\,}{c^2} \\ \end{gathered}

A=

c

2

kb

2

••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••••

(ノ^_^)ノ